Internal transcribed region (ITS) gene sequencing and pathogenicity study of Aeromonas veronii bv. sobria strain KTG3SB in juvenile red tilapia - Sezali, Rabi’atul ‘Adawiyah (2013)
The present study was conducted to identify the Aeromonas spp.by using Internal Transcribed Region (ITS) gene sequencing and to determine the virulence of the species. Five samples labelled TPK4B, PHE578L, KTG3SB, TPK2B and PK159S isolated from diseased freshwater fishes. The API test of all samples shows that the species wereA. sobria. In contrast, ITS sequence of three samples; TPK4B, PHE578L and KTG3SB were identified as A. veronii bv. sobria with similarity 97-98%. Another two samples TPK2B and PK159S were identified as A. culicicola and A. hydrophila respectively. Virulence of sample KTG3SB to juvenile red tilapia was also tested. 150 fish were injected through IP injection with different bacterial concentration (0.1x103 – 0.1x107 CFU/ml). Other 30 fish were injected with sterile PBS as negative control. The mortality recorded every two hours post challenge for three days. The LD50 calculated was 103 CFU/ml of treatment groups and fish shows symptom such as congestion, enlargement of gall bladder and abnormal swimming. The histology finding also shows some congestion in liver, spleen and gill. In the present study, ITS gene sequencing had proved that this method can definitely distinguish between intraspecific species and A. veronii bv. sobria had proved that it is very pathogenic to juvenile red tilapia.